Firm Expectations and News: Micro v Macro - Benjamin Born; Zeno Enders; Manuel Menkhoff; Gernot J. Müller; Knut Niemann; Gernot Müller (Center for Economic Studies and ifo Institute (CESifo), 2022)
In this study, we investigate how firm expectations about their own developments respond to different types of news. We classify news as either micro or macro, with micro news being information about firm-specific developments and macro news being information about the aggregate economy. Our analysis of firm surveys from Germany and Italy shows that both types of news consistently predict forecast errors, contradicting the idea of full-information rational expectations. Yet while firm expectations overreact to micro news, they underreact to macro news. We propose a model in which firms suffer from "island illusion" to explain these patterns in the data.
Keywords: D84; C53; E71; 330; firm expectations; survey; overreaction; underreaction; micro news; macro news; island illusion; business cycle